THE ANTAGONIST’S BETRAYAL IN NICHOLAS SPARK’S DEAR JOHN - Asrisyah Fitry Pulungan; Diana Sopha (Fakultas Sastra UMN AL Washliyah, 2021)
The antagonist’s betrayal in Nicholas Spark’s “Dear John” is the analysis of an antagonist’s betrayal named Savannah who had a boyfriend, John, as an army but she married another person named Tim instead of John, but then she confessed that she loved John again. Betrayal is a problem in human life causing a bad feeling of sadness and disappointment for the one who is betrayed. Using descriptive qualitative method,antagonist’s betrayal is found in two points. First her selfishness and secondly her love is given to another person. Her selfishness is further classified into doing something as she liked, neglecting John and being careless to Tim. Furthermore, her betrayal in loving another person is proven from her written expression through letter and her spoken confession of loving another person.